Model Tata Letak Gudang Penyimpanan Menggunakan Metode Class-Based Storage - Rini Alfatiyah; Sofian Bastuti; Riki Effendi (Fakultas Teknik UM Pontianak, 2021)
With many product characteristics, it is very vulnerable in the preparation of products and in the ideal capacity available. This happens in the warehouse. To find the ideal storage, an analysis of the warehouse layout is performed. The purpose of this study is to increase the warehouse's capacity and classify the products that are in the warehouse's storage locations. This Class-Based Storage method is a way of calculating and classifying based on the frequency of product movement. This research was carried out at PT. Cakra Satria Pratama in the warehouse. The results of this study indicate that the placement of the product is not ideal. Therefore, with the results of the proposed layout analysis results in the classification of products, when producing categories A, B and C with category A 53.85% of total products, category B 30.77% of total products and category C 15.38 % of the total products. Keyword: Layout; Class Based Storage Method; Warehouse.